IL-17 Aggravates Pseudomonas aeruginosa Airway Infection in Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Ding, Fengming; Han, Lei; Fu, Qiang; Fan, Xinxin; Tang, Rong; Lv, Chengjian; Xue, Yishu; Tian, Xue; Zhang, Min (Frontiers in Immunology, 2022)
Pseudomonas aeruginosa airway infection increases risks of exacerbations and mortality in chronic obstructive pulmonary disease (COPD). We aimed to elucidate the role of IL-17 in the pathogenesis. We examined the expression and influences of IL-23/IL-17A in patients with stable COPD (n = 33) or acute COPD exacerbations due to P. aeruginosa infection (n = 34). A mouse model of COPD (C57BL/6) was used to investigate the role of IL-17A in host inflammatory responses against P. aeruginosa infection through the application of IL-17A–neutralizing antibody or recombinant IL-17A. We found that P. aeruginosa infection increased IL-23/17A signaling in lungs of both COPD patients and COPD mouse models. When COPD mouse models were treated with neutralizing antibody targeting IL-17A, P. aeruginosa induced a significantly less polymorphonuclear leukocyte infiltration and less bacterial burden in their lungs compared to those of untreated counterparts. The lung function was also improved by neutralizing antibody. Furthermore, IL-17A-signaling blockade significantly reduced the expression of pro-inflammatory cytokine IL-1β, IL-18, TNF-α, CXCL1, CXCL15 and MMP-9, and increased the expression of anti-inflammatory cytokine IL-10 and IL-1Ra. The application of mouse recombinant IL-17A exacerbated P. aeruginosa-mediated inflammatory responses and pulmonary dysfunction in COPD mouse models. A cytokine protein array revealed that the expression of retinol binding protein 4 (RBP4) was down-regulated by IL-17A, and exogenous RBP4-recombinant protein resulted in a decrease in the severity of P. aeruginosa-induced airway dysfunction. Concurrent application of IL-17A-neutralizing antibody and ciprofloxacin attenuated airway inflammation and ventilation after inoculation of P. aeruginosa in COPD mouse models. Our results revealed that IL-17 plays a detrimental role in the pathogenesis of P. aeruginosa airway infection during acute exacerbations of COPD. Targeting IL-17A is a potential therapeutic strategy in controlling the outcomes of P. aeruginosa infection in COPD patients.